Effect of polyurethane sizing on carbon fibers surface and interfacial adhesion of fiber/polyamide 6 composites. Issue 16 (3rd January 2018) - Zhang, Tao; Zhao, Yueqing; Li, Hongfu; Zhang, Boming
ABSTRACT: Commercial epoxy sized carbon fibers (CFs) or unsized CFs have poor interfacial adhesion with polyamide 6 (PA6). Here, CFs are coated with polyurethane (PU) and their surface properties in terms of surface chemistry, contact angle, roughness, and morphology, are investigated. The results of Fourier transform infrared spectroscopy, X‐ray photoelectron spectroscopy, scanning electron microscopy, and atomic force microscopy demonstrate PU sizing evidently increases the quantity of polar functional groups on the CFs surface. The surface energy of the PU sized fiber is calculated according to the Owens–Wendt method. Compared with unsized fibers, the contact angle of PU sized fibers is decreased while their total surface energy is increased, indicating superior wettability. Moreover, transverse fiber bundle tests are performed to determine the interfacial adhesion between the CFs and PA6 matrix. The transverse fiber bundle strength of unsized CF is measured to be 12.57 MPa. For PU sized CFs processed with sizing concentration of 1.2%, this value is increased to 24.35 MPa, showing an increase of more than 90%. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46111. Abstract :